2009
DOI: 10.1002/lary.20477
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of treatment on survival in patients with advanced laryngeal carcinoma

Abstract: Primary surgical treatment is associated with improved survival for patients with stage IV disease and specifically T4 primary tumors. These data suggest that the observed national decrease in survival from laryngeal cancer may be due to a shift toward nonoperative treatment in that subset of patients with advanced primary disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
118
2
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 134 publications
(141 citation statements)
references
References 19 publications
(29 reference statements)
13
118
2
8
Order By: Relevance
“…According to the literature, survival rates for early (stages I and II), and late stage (stages III and IV) larynx cancers range between 73-92% and 35-64%, respectively. [20][21][22] fiengül et al reported that in the 50th month after the onset of therapy, the cumulative survival rate estimated for 172 patients in all disease stages was 69 percent. The cumulative survival rates in various disease stages were as follows: Stage I, 84%; II, 77%; III, 68%, and IV, 56%.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, survival rates for early (stages I and II), and late stage (stages III and IV) larynx cancers range between 73-92% and 35-64%, respectively. [20][21][22] fiengül et al reported that in the 50th month after the onset of therapy, the cumulative survival rate estimated for 172 patients in all disease stages was 69 percent. The cumulative survival rates in various disease stages were as follows: Stage I, 84%; II, 77%; III, 68%, and IV, 56%.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7] For example, Hoffman et al, 3 using a robust NCDB, reported that increased use of nonsurgical approaches for larynx preservation was concurrent with decreased relative survival in patients with T3 laryngeal cancers. However, because Hoffman et al 3 culled data from between 1985 and 2001, before the implementation of IMRT and the publication of RTOG 9001 and the more widespread use of induction and concurrent chemotherapy, their findings, although timely when published, do not accurately reflect the use of RT and combined modality techniques in the current era.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies' findings have implied that nonsurgical larynx preservation approaches may be associated with survival decrement. [3][4][5][6][7] Specifically, Hoffman et al, 3 using large-scale series from the National Cancer Data Base (NCDB), reported that the increased use of organ preservation approaches was associated with a decrement in relative survival in patients with T3 laryngeal cancer. Gourin et al, 4 in a retrospective series of locally advanced disease, demonstrated that nonsurgical larynx preservation was associated with poorer survival particularly for patients with T4 disease.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations